Poblaciones de eufasidos de la región del Estrecho de Bransfield y adyacencias: Primera Expedición Antartica Brasileña. Verano 1982-1983 (2.a fase) - Montú, Mónica; Fernandes, Luiz Fernando Loureiro; Oliveira, Ildo Ritter de; Cordeiro, Tarcisio Alves (Universidade Federal do Paraná, 2022)
Horizontal and vertical distribution of Euphausia superha, E. frigida, E. crystallorophias, Thysanoessa macrura and I . vicina populations were studied between January 31st and February 9th in 28 stations of the Bransfield Strait. The population structure and size frequency are analized. The results obtained suggest the existence of: 1) a local population of krill in the Bransfield Strait, 2) recruitment areas near the Palmer Archipelago and Elephant Island, and 3) Thysanoessa macrura populations originated, possibly, in adjacent regions of Palmer Archipelago and Bellingshausen Sea. The vertical distribution was described considering the larvae and post-larvae layer preference. The relation krill-phytoplankton during this period was analized too. Durante el período 31 de enero — 9 de febrero de 1983 fue realizada la 2.a fase de la 1.a Expedición Antártica Brasiíena por el barco “ Prof. W. Bernard” , navio perteneciente al Instituto Oceanográfico de la Universidad de San Pablo (IOUSP). Los trabajos de muestreo fueron desarrollados en la región dei Estrecho de Bransfield y el programa respondia a las recomendaciones efectuadas para el “ First International BíOMASS Experiment” En este trabajo se analizan los resultados obtenidos dei material de Eufausidos recolectados. Descreve-se a distribuição horizontal e vertical das populações de eufáusidos: Euphausia superba, E. frigida, E. crystallorophias, Thysanoessa macrura e T. vicina. São analisadas a estrutura populacional e a freqüência de tamanhos em 28 estações localizadas na região do 'Estreito de Bransfield durante o período de 31/01 a 09/02/83. Os resultados sugerem a existência de: 1) uma população local de krill no'Estreito de Bransfield; 2) áreas de recrutamento nas regiões próximas ao Arquipélago de Palmer e Ilha Elefante; 3) populações de Thyanoessa macrura supostamente originadas em regiões adjacentes ao Arquipélago de Palmer e Mar de Bellingshausen. A distribuição vertical dos eufáusidos é descrita considerando- se a preferência dos estádios larvais e ...